(untitled) (International Journal of Engineering and Computer Science, 2013)
Steganography gained importance in the past few years due to the increasing need for providing secrecy in an open environment like the internet.Steganography is the art of hiding the fact that communication is taking place, by hiding information in other information. Many different carrier file formats can be used, but digital images are the most popular because of their frequency on the internet Steganography is used to conceal the information so that no one can sense its existence.In most algorithm used to secure information both steganography and cryptography are used together to secure a part of information. Steganography has many technical challenges such as high hiding capacity and imperceptibility. In this paper,we try to optimize these two main requriments by proposing a novel technique for hiding data in digital images by combining the use of adaptive hiding capacity function that hides secret data in the integer wavelet coefficients of the cover image with the optimum pixel adjustment (OPA) algorithm.The coefficients used are selected according to a pseudorandom function generator to increase the security of the hidden data.The OPA algorithm is applied after embedding secret message to minimize the embedding error.The proposed system showed high hiding rates with reasonable imperceptibility compared to other steganographic system.